Musculo Skeletal Disorders in Dentistry - Bindra, Parvinder; Ahluwalia, Rajiv; Kumar, Ankur; Kumar, Priyanka Sethi; Verma, Deepa; Mittal, Mitushi (Journal of Orofacial Research, 2017)
In dental practice knowledge of patients and operator’s position is important for the health and comfort of both patient and operator. The causes of musculoskeletal disorders in dentistry are multi factorial, ranging from non-ergonomic loupes and improper selection of delivery systems, to generic exercise that worsens muscle imbalances. Therefore proper operator positioning techniques help in preventing the progression toward chronic pain or potential injury for the operator.